2009
DOI: 10.4161/cc.8.3.7642
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic function of checkpoint kinase-2 in syncytia elicited by the HIV-1 envelope

Abstract: Fusogenic HIV-1 isolates induce the fusion of infected and bystander cells. Such syncytia can be found as "multinucleated giant cells" in the brain from HIV-1-infected individuals, as well as in lymphoid tissues. Syncytia elicited by the HIV-1 envelope glycoprotein (Env) manifest the aggregation of PML in discrete nuclear bodies and the recruitment of TopBP1, NBS1 and ATM to DNA damage foci containing phosphorylated ATM and histone H2AX (g-H2AX). This DNA damage response then culminates in p53-dependent activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…The presence of multiple disseminated foci composed of microglia, macrophages and multinucleated giant cells is a hallmark of complex dementia in adults [5,30]. However, we did not find multinucleated giant cells in the samples of any children with HIV-EP included in the study.…”
Section: Discussioncontrasting
confidence: 62%
“…The presence of multiple disseminated foci composed of microglia, macrophages and multinucleated giant cells is a hallmark of complex dementia in adults [5,30]. However, we did not find multinucleated giant cells in the samples of any children with HIV-EP included in the study.…”
Section: Discussioncontrasting
confidence: 62%
“…33 Similarly, depletion of Chk1 accelerates the spontaneous apoptosis of polyploid cells resulting from aberrant cell fusion. 35 We also found that the knockdown of endonuclease G killed tetraploid colon cancer cells, a result that could be recapitulated by eliminating endonuclease G from the genome of tetraploid yeast cells. 36 at 30-40% confluence by means of the HiPerFect transfection reagent (Qiagen, Hilden, Germany) as previously described.…”
Section: Resultsmentioning
confidence: 80%
“…10 Thus, the inhibition of Chk1 was shown to kill tetraploid cells through a pathway that involves the p38 MAPK -dependent activation of p53, 11 followed by p53-dependent activation of Bax-/Bak-dependent mitochondrial outer membrane permeabilization (MOMP). [12][13][14][15] Because the aforementioned results were obtained in transformed cells, they cannot be extrapolated to the physiology of Report p53 represses the polyploidization of primary mammary epithelial cells by activating apoptosis primary non-transformed cells, in which the suppression of tetraploidy ensured by apoptosis might constitute a barrier against oncogenesis. Therefore, we decided to reinvestigate the contribution of p53 and apoptosis to the inhibition of tetraploidization in primary epithelial cells from the mammary gland.…”
Section: Introductionmentioning
confidence: 99%